Design and Operation of the Lombardy Parkinson's Disease Network - Albanese, Alberto; Di Fonzo, Alessio; Fetoni, Vincenza; Franzini, Angelo; Gennuso, Michele; Molini, Graziella; Pacchetti, Claudio; Priori, Alberto; Riboldazzi, Giulio; Volonté, Maria Antonietta; Calandrella, Daniela (Frontiers in Neurology, 2020)
Background. Parkinson’s disease (PD) is one of the most common chronic neurological conditions leading to disability and social burden. According to the 2016 Italian National Plan on Chronic Diseases, regional health authorities are implementing dedicated networks to manage neurological diseases, including PD. Methods. A panel of experts representing health-care providers in Lombardy reached consensus on the organization of a patient-centered regional PD healthcare network. Results. The panel proposed a structure and organization implementing a hub-and-spoke PD network model. Three levels of neurological services were identified: General Neurologist, PD Clinic, PD Center. This model was applied to health service providers currently accredited by the Lombardy health service, yielding 12 candidate PD Centers, each serving an area of approximately 1’000-2’000 km2, and not less than 27 PD Clinics. The panel agreed on uniform diagnostic and staging criteria for PD, and on a minimum common clinical data set, on PD patient management by the network at initial and follow-up assessments, on the cadence of follow-up visits, on patient referrals, and on outcome measures for the assessment of network activities. Conclusions. The implementation of disease-centered networks for chronic neurological disease provides an innovative opportunity to improve patient management, facilitate research and education.